Electrical conductivity and dielectric properties of Sr doped M-type barium hexaferrite BaFe12O19. Issue 3 (5th January 2021) - Marouani, Y.; Massoudi, J.; Noumi, M.; Benali, A.; Dhahri, E.; Sanguino, P.; Graça, M. P. F.; Valente, M. A.; Costa, B. F. O.
Abstract : The hexaferrite Ba1− x Sr x Fe12 O19 compounds with x = 0, 0.5 and 1 were synthesized by the autocombustion method. Abstract : The hexaferrite Ba1− x Sr x Fe12 O19 compounds with x = 0, 0.5 and 1 were synthesized by the autocombustion method. X-ray diffraction (XRD), Raman spectroscopy and transmission electron microscopy (TEM) were used for structural and morphological studies.